Upaya Peningkatan Keaktifan Belajar Ekonomi Melalui Penggunaan Metode Discovery Learning Pada Siswa Kelas X 2 Sma Negeri 1 Polanharjo Tahun Ajaran 2015/2016 - Silvia, Lisa, Drs. Budi Sutrisno, M.Pd (2017)
Class Action Research aims to improve students' learning activeness on economic subjects through a learning model Discovery Learning (Invention). The research subject is class X 2 SMA Negeri 1 Polanharjoyang totaled 18 students. Data collection methods used were observation, interviews, field notes and documentation. To ensure the validity of data used triangulation techniques. Data analysis technique used consisted of data reduction, data presentation and verification of data. The results showed an increase in the activity of students in the learning economy through the application of learning models Discovery Learning (Invention). It can be seen from 1) activity of students participating in performing the task of learning before the action amounted to 33.33% and after the action to be 100%. 2) Students who engage in problem solving before the action amounted to 27.77% and to 83.33% after the action. 3) Students who dared to ask other students or teachers before actions 22.22% and amounted to 66.66% after the action. 4) Students are trying to find the information needed to solve the problem before the action amounted to 27.77% and amounted to 61.11% after the action. 5) Students who carry out the corresponding command group discussions teacher before action by 16.66% and amounted to 55.55% after the action. 6) students assess her abilities and the results obtained prior to action by 11.11% and after action by 50%. From the research results support the hypothesis "if the learning economy through the application of learning models Discovery Learning is done properly and appropriately, it can enhance the activity of students in the learning economy".